Business Environment, Entrepreneurial Competence, and Innovativeness: Evidence from Bandung’s Embroidery SMEs - Eka Ludiya; Agus Rahayu; Hari Mulyadi; Lili Adi Wibowo; Asep Kurniawan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
In a dynamic and competitive business environment, understanding the factors that drive entrepreneurial innovation is important. This study examines the relationship between entrepreneurial competence and innovation in the context of the embroidery industry in Bandung. Structural Equation Modeling was employed to evaluate the proposed relationships with 90 embroidery entrepreneurs in Bandung. Empirical results show that a conducive business environment is associated with higher levels of innovation among embroidery entrepreneurs in Bandung. In addition, these environmental conditions also strengthen entrepreneurial competence, which in turn drives innovation, with entrepreneurial competence acting as a partial intermediary mechanism in this relationship. This study contributes to the literature on entrepreneurship and innovation by providing empirical evidence confirming the importance of entrepreneurial competence as a mechanism linking environmental conditions and innovation outcomes in small-scale creative industries. Furthermore, the findings emphasize the importance of improving the business environment to encourage entrepreneurial creativity, suggesting that policymakers and local stakeholders need to strengthen their support through access to resources, market information, and institutions. The research any several limitations. First, focuses on entrepreneurs in the embroidery industry in Bandung. This contextual focus suggests that the findings are most relevant to the embroidery sector in Bandung and may not fully reflect conditions in other settings. Second, the study relies on primary data collected through questionnaires, which may be subject to respondents’ perceptions and interpretations.